2013
DOI: 10.3923/jpt.2014.1.24
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Alpha-lipoic Acid and Melatonin Against Cadmium-induced Oxidative Stress in Erythrocytes of Rats

Abstract: Cadmium (Cd) is a well-known human carcinogen and a potent nephrotoxin. The protective effects of alpha-lipoic acid and melatonin against cadmium (Cd) induced oxidative stress to erythrocytes in rats were evaluated. One hundred male albino rats were divided into five groups containing 20 rats each. Group I: (control) administered distilled water. Group II :(Cadmium exposed group) received cadmium chloride (4.4 mg/kg body weight of 1/20th of LD50 / day) orally for 10 weeks. Group III :(Cadmium +alpha-lipoic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 68 publications
(47 reference statements)
2
9
0
Order By: Relevance
“…On the other hand, abovementioned enzyme levels decreased due to Mlt administration in Mlt and Cd + Mlt group animals in present study. These results were consistent with Alabbassi et al (2008) and Hussein et al (2014). Besides, T.pro and Alb levels were found the lowest in Cd group in this study.…”
Section: Discussionsupporting
confidence: 94%
“…On the other hand, abovementioned enzyme levels decreased due to Mlt administration in Mlt and Cd + Mlt group animals in present study. These results were consistent with Alabbassi et al (2008) and Hussein et al (2014). Besides, T.pro and Alb levels were found the lowest in Cd group in this study.…”
Section: Discussionsupporting
confidence: 94%
“…It was established that lead induce oxidative damage and lipid peroxidation in different organs (Hamadouche et al, 2009). Similar results were observed by Hussein et al, (2014) who revealed that, lead intoxicated rats showed significant increase in erythrocytes MDA concentration when compared with normal control group. Furthermore, Omobowale et al, (2014) found a significant increase in MDA and H2O2 generation in the liver and the erythrocytes following exposure to lead.…”
Section: Discussionsupporting
confidence: 78%
“…LA is a water-and fat-soluble, sulfur-containing compound proven as a metal chelator (Al-Majed et al, 2002). Previous studies have demonstrated that LA has a protective effect on Cd-induced oxidative stress (Veljkovic et al, 2012;Hussein et al, 2014), however, the underlying mechanism is not clear.…”
Section: Introductionmentioning
confidence: 99%